Mobile EEG in Education & Language Learning: A Scoping Review - Jincai Yang; Craig Neville; Máire Ní Riordáin (Journal of Neuroeducation)
Mobile Electroencephalography (mEEG) has emerged as a promising tool for studying cognitive processes in naturalistic learning environments. Unlike traditional EEG, mEEG offers portability, allowing real-time brain activity monitoring in classroom settings. This systematic literature review, conducted following Scoping guidelines, examines research on mEEG applications in educational contexts between 2010 and 2025. The review explores trends in mEEG technology, its use across disciplines, and its potential for understanding cognitive functions such as attention, memory, and cognitive load. Findings indicate that mEEG has been predominantly applied to investigate student engagement and brain-to-brain synchrony, yet its use in language learning remains limited. The review highlights advantages such as improved ecological validity, increased accessibility, and interdisciplinary potential but also identifies challenges including data reliability, motion artifacts, and ethical concerns. Despite these limitations, mEEG presents an opportunity to bridge neuroscience and education, offering insights into real-world cognitive engagement that could inform pedagogical strategies. The findings emphasize the need for further longitudinal research to explore mEEG’s role in multilingual and instructed language learning contexts. This review contributes to the growing discourse on neuroeducation, advocating for expanded research on mEEG in diverse educational settings.